Ambient Assisted Living 8. AAL-Kongress 2015,Frankfurt/M, April 29-30. April, 2015 - Wichert, Reiner; Klausing, Helmut (Advanced Technologies and Societal Change,, 2016)
In this book, leading authors in the field discuss developments of Ambient Assisted Living. The contributions have been chosen and invited at the 8th AAL Congress, Frankfurt/M. The meeting presents new technological developments which support the autonomy and independence of individuals with special needs. The 8th AAL Congress focusses its attention on technical assistance systems and their applications in homecare, health and care.